1997
DOI: 10.1021/js960529n
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Absorption Enhancers on the Transport of Model Compounds in Caco-2 Cell Monolayers: Assessment by Confocal Laser Scanning Microscopy

Abstract: Three typical absorption enhancers, i.e., sodium caprate (Cap-Na), sodium deoxycholate (Deo-Na), and dipotassium glycyrrhizinate (Grz-K), were compared in terms of their permeability-enhancing effects on hydrophilic and hydrophobic model compounds in Caco-2 cell monolayers. The transepithelial electrical resistance (TEER) of the monolayers was reduced concentration-dependently by treatment with Cap-Na and Deo-Na, while treatment with Grz-K increased the TEER. Two patterns of TEER reduction were observed: one p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(54 citation statements)
references
References 20 publications
4
50
0
Order By: Relevance
“…Studies have reported that bile salts enhance the epithelial transport of hydrophilic drugs through the paracellular route and that of hydrophobic compounds through both paracellular and transcellular routes (Sasaki et al, 1997;Shimazaki et al, 1998). Since lovastatin is lipophilic, the enhanced bioavailabilities by the addition of bile salts were thought to be due to the increased transport via both paracellular and transcellular routes.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that bile salts enhance the epithelial transport of hydrophilic drugs through the paracellular route and that of hydrophobic compounds through both paracellular and transcellular routes (Sasaki et al, 1997;Shimazaki et al, 1998). Since lovastatin is lipophilic, the enhanced bioavailabilities by the addition of bile salts were thought to be due to the increased transport via both paracellular and transcellular routes.…”
Section: Resultsmentioning
confidence: 99%
“…We highlight Keegan's studies, reported mainly in the form of conference abstracts, to draw attention to a situation in which alternative modes of sugar absorption might be important. In both mammalian and avian species the paracellular route of absorption of water soluble compounds has been visualized using either autoradiography [of radiolabeled polyethylene glycol (Ma et al, 1993)] or confocal laser microscopy [using fluorescein Hurni et al, 1993;Sakai et al, 1997)], its molecular size selectivity has been characterized using a series of nonelectrolyte water-soluble probes that differ in molecular dimension (Chediack et al, 2003;Ghandehari et al, 1997;Hamilton et al, 1987), and its charge selectivity has been characterized using relatively inert, charged peptides (Chediack et al, 2006;He et al, 1998). Our goal was to quantify the level of possible nonmediated absorption.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the equilibration point for the FITC-labeled dextran 150 was not reached after 48 hours of incubation ( Figure 2C). The BBB permeation of FITC-dextran system was severely obstructed because of the extensive branching behavior occurring at greater molecular weight (MW 10 kDa) [32][33][34] , high hydrophilic properties (logP =-2.0 for FITC-dextran 4 kDa), 35 and topological polar surface area of dextrans (268.68 Å 2 ). To eliminate the possibility of FITC disintegration from dextran polymer, the FITC molecule was also covalently attached to dextran via random conjugation with any free hydroxyl group at a frequency of 0.003 to 0.02 moles of FITC per mole of glucose.…”
Section: Resultsmentioning
confidence: 99%